Implementasi Bantuan Sosial pada Era Pandemi Covid-19: Evaluasi Aspek Transparansi dan Akuntabilitas - Dumilah Ayuningtyas; Humaatul Islam; Sahfira Ulfa Hasibuan; Cindy Margaretha; Naurah Naziihah; Nisa'atul Maharanita Fitrianingrum; Ayudina Larasanti; Qurrata Ayuni (Komisi Pemberantasan Korupsi, 2022)
The Covid-19 virus has spread worldwide at an alarming rate, infecting millions who are expecting government assistance during the pandemic. This research aimed to evaluate the distribution process of the social assistance provided by the Indonesian government during the Covid-19 pandemic. A quick online survey was conducted on 279 respondents from 12 provinces in Indonesia. Furthermore, interviews were also conducted with seven informants to strengthen the quick survey's results, a form of triangulation method. The results show that most respondents felt that the distribution of social assistance during the pandemic was not transparent and on target, partly due to separate budget allocations between several ministries, inaccurate data and unintegrated data. Strengthening the role of local government and increasing the involvement of community organizations as well as the flexibility to adjust the form and mechanism of social assistance, are the recommendations of this study.